Moringa oleifera leaf meal as an environmental friendly protein source for ruminants: Biomethane and carbon dioxide production, and fermentation characteristics. (1st November 2017) - Elghandour, M.M.Y.; Vallejo, L.H.; Salem, A.Z.M.; Mellado, M.; Camacho, L.M.; Cipriano, M.; Olafadehan, O.A.; Olivares, J.; Rojas, S.
Abstract: Ruminal fermentation produces methane (CH4 ) and carbon dioxide (CO2 ) which contribute to global warming. Therefore, several enteric CH4 and CO2 mitigation strategies have been explored recently. In this trial the effect of replacing soybean meal, as the sole protein source in a control total mixed ration (TMR) with Moringa oleifera leaf meal (MLM) at different levels, on ruminal fermentation characteristics were studied. M. oleifera leaf meal replaced (g/100 g DM): 0 (TMR0, control), 10 (TMR10), 20 (TMR20), 30 (TMR30), 40 (TMR40), 50 (TMR50), 60 (TMR60), 70 (TMR70), 80 (TMR80), 90 (TMR90), and 100 (TMR100) of soybean meal in the rations. Rations were incubated for 48 h using rumen inoculums from goats and steers. Some interactions between inoculum × TMR were observed ( P  < 0.05) for gas production (GP) parameters, CH4 production, and fermentation profile. Moreover, most parameters determined responded differently between animal species. Rations containing MLM decreased the asymptotic GP ( P  < 0.01), while they increased ( P  < 0.01) the rate of GP and lag of GP with both inoculums. Decreased ( P  < 0.05) CH4 production and increased CO2 production ( P  < 0.05) were observed when MLM replaced soybean meal. Diets containing MLM decreased ( P  < 0.05) ruminal ammonia-N and total protozoal number, while increasing ( P  < 0.05) total bacterial number with both goat and steer inoculums. Replacing soybean meal with MLM increased ( P  < 0.05) fermentation pH, but decreased ( P  < 0.05) organic matter degradability (OMD) with goat inoculum. Conversely, a declined ( P  < 0.05) in SCFA concentrations, and enhanced ( P  < 0.05) OMD and DM degradability compared with the control diet was observed with diets containing MLM. It is concluded that replacing soybean meal in goat and steer diets negatively affected the nutritive value of diets but decreased CH4 production. From an environmental standpoint, the replacement of soybean meal with MLM is a potential sustainable strategy to reduce CH4 production from goats and steers, and thus mitigate greenhouse gas emissions. Goat inoculum was more efficient in reducing CH4 production than that of steers. Graphical abstract: Highlights: Replacing soybean with M. oleifera negatively affected ruminal fermentation. Fermentation differed between goat and steer inoculums. M. oleifera decreased methane production. M. oleifera can be used for the sustainable mitigating of environmental pollution from ruminants.